Novel institutions : anachronism, Irish novels and nineteenth-century realism - Mullen, Mary L. (Edinburgh critical studies in Victorian culture., 2019)
This book examines anachronisms in realist writing from the colonial periphery to redefine British realism and rethink the politics of institutions. Paying unprecedented attention to nineteenth-century Irish novels, it demonstrates how institutions constrain social relationships in the present and limit our sense of political possibilities in the future. It argues that we cannot escape institutions, but we can refuse the narrow political future that they work to secure. -- Publisher description.